2015
DOI: 10.7224/1537-2073.2014-006
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Biofeedback as a Psychological Intervention in Multiple Sclerosis: A Randomized Controlled Study

Abstract: Background: Relaxation, mindfulness, social support, and education (RMSSE) have been shown to improve emotional symptoms, coping, and fatigue in multiple sclerosis (MS). Biofeedback was trialed as a psychological intervention, designed to improve self-control, in two groups of patients with MS. Both groups received RMSSE, and one group additionally received biofeedback.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 41 publications
(64 reference statements)
0
13
0
Order By: Relevance
“…Excluded studies with the main reasons for exclusion are shown in Table A2 in Appendix. The quality of studies ranged from weak to strong; 10 studies ( 40 46 , 49 , 52 , 53 ), 4 studies ( 35 , 47 , 48 , 50 , 55 ), and 6 studies ( 33 , 34 , 39 , 51 , 54 , 56 , 57 ) had a global rating of strong, moderate, and weak, respectively (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Excluded studies with the main reasons for exclusion are shown in Table A2 in Appendix. The quality of studies ranged from weak to strong; 10 studies ( 40 46 , 49 , 52 , 53 ), 4 studies ( 35 , 47 , 48 , 50 , 55 ), and 6 studies ( 33 , 34 , 39 , 51 , 54 , 56 , 57 ) had a global rating of strong, moderate, and weak, respectively (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies (13 articles) ( 35 , 39 50 ) with sufficient data were included in our meta-analyses. Table A3 in Appendix outlines reasons why the remaining eight studies (nine articles) ( 33 , 34 , 51 57 ) were not included in the meta-analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, cognitive variables, such as symptom focusing and believing symptoms are a sign of damage, have been found to change significantly after CBT in patients with MS and high levels of fatigue (Knoop et al ., ). The other possibility is that the cognitive and physical tasks used here could be deployed as behavioural experiments, in which patients are provided feedback about actual impairment, similar to the use of actigraphy feedback in insomnia (Tang & Harvey, ), or use of biofeedback in fatigued patients with MS (Mackay et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…A study that evaluated psychological interventions for patients with MS in which the experimental group carried out the Biofeedback technique with the RMP and Respiration technique and where the control group just practiced RMP and the Respiration technique, showed that improvements were made in perceived stress for both groups. It was suggested that this was the case due to, in part, the daily practice of RMP with the Respiration technique 24 .…”
Section: Discussionmentioning
confidence: 99%